Invasive Group B Streptococcal Disease in Two Pediatric Patients with Systemic Lupus Erythematosus - Dongning Wu; Kenneth Bromberg; Roberto Jodorkovsky (Case Reports in Pediatrics)
Systemic lupus erythematosus (SLE) is an autoimmune disease associated with high morbidity and mortality, often caused by infection. We report two patients with SLE who were treated with steroids and immunosuppressive medication and then developed invasive Group B Streptococcus (GBS) infections. While GBS infection is rare in the nonneonatal pediatric age group, GBS should be considered when treating SLE patients presenting with signs of infection.